Does the Legal Form Matter for Firm Performance in the MENA Region? - Issam Abdo Ahmad; Ali Fakih (Institute of Labor Economics (IZA), 2021)
This paper attempts to study the relationship between firm legal form and firm performance in the Middle East and North Africa Region (MENA) using the World Bank Enterprise Survey (WBES) database. Our analysis shows that open shareholding, closed shareholding, partnership, and limited partnership companies demonstrate an advantage in terms of annual sales and annual productivity growth rates over sole proprietorship firms, and that medium-sized and large-sized firms also demonstrate an advantage over small ones. Our analysis also shows that foreign ownership, exporting activities, the usage of the web in communication with clients and suppliers, and the presence of full-time workers positively affect firm performance. These findings are robust when running the analysis for firms with female participation in ownership. This paper provides directions for strategists targeting at improving the performance of firms.
Keywords: C10; G30; L25; 330; legal form; firm performance; MENA region